Pengaruh Lingkungan Kerja Terhadap Kerja Sama Pegawai Pada Kantor Badan Pusat Statistik Kabupaten Wajo - Darmawan Darmawan; Burhanuddin Burhanuddin (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
The success of an organization is based on the ability of its members to work together, determined by a good work environment. The work environment emphasizes the pleasant feeling of the organizational atmosphere, not only from the physical condition but also from all internal aspects of the organization. Thus, the work environment that develops in an organization will be pleasant or unpleasant for the employees concerned. This research is census research, namely research whose data sources are all members of the population, with the main data collection technique being a questionnaire. Using a quantitative approach with descriptive and associative study methods. The descriptive method is a method for finding out the value of an independent variable to be connected or compared with other variables, the associative method is a method intended to connect a variable with other variables. The results of research data analysis on the Work Environment and Collaboration prove that the Work Environment at the Central Statistics Agency Office is in the good category. Likewise, the Cooperation variable is in the Very Good category. The influence that the Work Environment variable has on Collaboration is in the very strong category and the direction of the relationship is positive and the data is significant. The conclusions that can be obtained from this research are as follows. The work environment for staff at the Wajo Regency National Staristic Agency Office is in the good category. Cooperation between employees of the Wajo Regency National Staristic Agency Office is in the Very Good category. The results of data analysis show that the influence provided is a strong influence with a positive and significant relationship direction.